NEUTRON ACTIVATION LOGGING OF OXYGEN, SILICON AND ALUMINUM AND RECONSTRUCTION OF THE FLUID TYPE IN QUARTZ-FELDSPAR RESERVOIR ROCKS - Khisamutdinov A.I.; Blankov Y.B. (My University, 1989)
The present array of tools for the geophysical investigations of oil wells is incapable of determining the liquid content (water or oil) of the rock pores in the conditions typical of wells of Western Siberia, which contain formation waters of low salinity and are drilled in polymict reservoir rocks of complex mineral compositions. The reason for the difficulty in interpreting the data of neutron activation logging involves the comparability of variations in the oxygen content of the fluid in the pores with variations of oxygen content in the rock frame. It has been suggested that three indicator elements (O, Si, and Al) should be used to evaluate the water and gas content from neutron activation logging data. The authors present the authors present a theoretical model that can be used to reconstruct the fluid type from activation logging data on O, Si and Al.